Vaginal Probiotics for Reproductive Health and Related Dysbiosis: Systematic Review and Meta-Analysis - López-Moreno, Ana; Aguilera, Margarita (Journal of clinical medicine, 2021)
The use of probiotics in reproductive-related dysbiosis is an area of continuous progress due to the growing interest from clinicians and patients suffering from recurrent reproductive microbiota disorders. An imbalance in the natural colonization sites related to reproductive health—vaginal, cervicovaginal, endometrial, and pregnancy-related altered microbiota—could play a decisive role in reproductive outcomes. Oral and vaginal administrations are in continuous discussion regarding the clinical effects pursued, but the oral route is used and studied more often despite the need for further transference to the colonization site. The aim of the present review was to retrieve the standardized protocols of vaginal probiotics commonly used for investigating their microbiota modulation capacities. Most of the studies selected focused on treating bacterial vaginosis (BV) as the most common dysbiosis; a few studies focused on vulvovaginal candidiasis (VVC) and on pretreatment during in vitro fertilization (IVF). Vaginal probiotic doses administered were similar to oral probiotics protocols, ranging from ≥107 CFU/day to 2.5 × 1010 CFU/day, but were highly variable regarding the treatment duration timing. Moderate vaginal microbiota modulation was achieved; the relative abundance of abnormal microbiota decreased and Lactobacillus species increased.